Validity Test of Moodle-Based Digital Assessment to Measure Science Literacy Skills in Environmental Pollution Material - Annisaa Dwi Ayu Permatasari; Rif'ati Dina Handayani; Bea Hana Siswati (Universitas Pendidikan Mandalika, 2023)
This study aims to test the level of validity of Digital Assessment based Moodle as an assessment instrument to measure scientific literacy skills possessed by SMP/MTs students, especially on environmental pollution material. This method of research was development research with a 4D model consisting of a defining stage (Define), planning level (Design), development stage (Develop), and spread level Disseminate. At the development stage or development validation was carried out Digital Assessment based Moodle by expert validators consisting of 2 Lecturers in Science Education Master’s Degree at the University of Jember and 3 Science Teachers from SMPN 1 Jember, SMPN 2 Jember and SMPN 1 Probolinggo. The data analysis technique used was descriptive analysis and percentage calculation of validation results. The validation results in Digital Assessment-based Moodle obtained an average of 94.1% with a very valid category so that Digital Assessment-based Moodle met the quality and could be applied to students of class VII SMP SMP/MTs to measure students' scientific literacy skills, especially on environmental pollution material.